2015
DOI: 10.1111/cmi.12474
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofHelicobacter pylori VacA-containing vacuoles (VCVs), VacA intracellular trafficking and interference with calcium signalling in T lymphocytes

Abstract: The human pathogen Helicobacter pylori colonizes half of the global population. Residing at the stomach epithelium, it contributes to the development of diseases such as gastritis, duodenal and gastric ulcers, and gastric cancer. A major factor is the secreted vacuolating toxin VacA, which forms anion-selective channels in the endosome membrane that cause the compartment to swell, but the composition and purpose of the resulting VacA-containing vacuoles (VCVs) are still unknown. VacA exerts influence on the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 77 publications
1
38
0
1
Order By: Relevance
“…Intracellular free Ca 2+ is a critical factor for activation of phagocytes such as inducing phagocytosis, the respiratory burst, maturation of phagosomes, and secretion of bactericidal substances [71]. Previous studies showed that high [Ca 2+ ]i is involved in killing intracellular Listeria monocytogenes and Helicobacter pylori [71,72]. In the present study, we revealed that the total ROS and NO levels and [Ca 2+ ]i in the L .…”
Section: Discussionsupporting
confidence: 53%
“…Intracellular free Ca 2+ is a critical factor for activation of phagocytes such as inducing phagocytosis, the respiratory burst, maturation of phagosomes, and secretion of bactericidal substances [71]. Previous studies showed that high [Ca 2+ ]i is involved in killing intracellular Listeria monocytogenes and Helicobacter pylori [71,72]. In the present study, we revealed that the total ROS and NO levels and [Ca 2+ ]i in the L .…”
Section: Discussionsupporting
confidence: 53%
“…A classical feature of VacA activity is its capability to induce vacuoles in host cells. In a recent study, the composition of these vacuoles was analyzed by mass spectrometry . A set of 122 specific proteins implicated in immune responses, cell death, and cell signaling were identified.…”
Section: Novel Vaca and Caga Studiesmentioning
confidence: 99%
“…A set of 122 specific proteins implicated in immune responses, cell death, and cell signaling were identified. VacA also interacts with proteins from the endoplasmic reticulum and Golgi, which identified these two compartments as new VacA targets . Another report showed that a stem‐loop structure in the 5′ untranslated region of the vacA transcript is important for vacA transcription and toxin activity .…”
Section: Novel Vaca and Caga Studiesmentioning
confidence: 99%
“…10 The suppression is resulting into inhibition of activation and proliferation of T cell causing induction of cell cycle arrest. In order to block calcineurin, VacA inhibits calcium influx after preventing ER calcium sensing protein STIM1 to bind with calcium release activated calcium (CRAC) Channel protein, ORAI1.…”
mentioning
confidence: 99%
“…This may subsequently lead to the blocking at the level of Ca 2+ calmodulin dependent phosphatase calcineurin 10. It is reported that VacA suppresses nuclear translocation of NFAT thereby causing downregulation of interleukin-2 (IL2) gene transcription.…”
mentioning
confidence: 99%